Pengaruh Financial Literacy dan Modal Investasi terhadap Trading Activity Investor Pemula di Bursa Efek Indonesia - Frima, Rini; Husni, Tafdil; Hamidi, Masyhuri; Adrianto, Fajri (Owner : Riset dan Jurnal Akuntansi, 2024)
This empirical study aims to test and analyze the influence of financial literacy and investment capital on the trading activity of beginner investors on the Indonesia Stock Exchange (BEI). This research was conducted on Politeknik Negeri Padang Accounting Department students who have had a Rekening Dana Nasabah (RDN) on the IDX for less than 1 (one) year. The research sample is students who have taken courses in financial management and capital markets. The trading activity observed is the frequency of share buying and selling transactions on the IDX from April 1 to June 30, 2022. Investment capital is the amount of rupiah deposited to RDN at the start of the transaction. 54 respondents participated in this research and the data was processed. The data obtained were processed and analyzed using descriptive statistical and multiple linear regression using SPSS 26. The results of the study showed that partially, investment capital had a positive effect on trading activity, while financial literacy did not affect trading activity. However, the investment capital and financial literacy variables influence the trading activity of beginner investors on the IDX in 2022.